Transoral robotic salivary surgery for hilar\parenchymal submandibular stones - Capaccio, Pasquale; Lazzeroni, Matteo; Torretta, Sara; Solimeno, Lorenzo Salvatore; Cristofaro, Valentina; Proh, Michele; Cammaroto, Giovanni; Meccariello, Giuseppe; Vicini, Claudio; Pignataro, Lorenzo (Frontiers in Surgery, 2024)
ObjectivesA prospective interventional study was designed to describe our series of patients with submandibular stones undergoing sialendoscopy-assisted TORSS (trans-oral robotic salivary surgery) by means of Si or Xi Da Vinci robotic system between January 2019 and June 2023, in order to assess safety and effectiveness of the procedure.Methods54 adult patients with submandibular stones undergoing sialendoscopy-assisted TORSS between January 2019-June 2023.ResultsThe global success rate was 81.5%, with better surgical outcomes in patients with palpable hilar/hilo-parenchymal stones compared to non-palpable pure parenchymal ones (92.7 vs. 46.2%). In addition, the mean stone size in cases failing TORSS was smaller than that documented in successfully treated patients (7.8 ± 1.8 vs. 9.8 ± 2.4 mm). No major untoward effects were observed (transitory lingual nerve dysfunction in 3 patients undergoing Xi Da Vinci surgery). A positive outcome in terms of post-operative surgical pain, patient's satisfaction and recovery time was observed.ConclusionsIntrinsic stone features (such as size, location/palpability) seems to be predictor for surgical success; an accurate pre-operative planning is mandatory to better select which patient can benefit most from TORSS procedure.